2015
DOI: 10.1149/2.0061506eel
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Drying Synthesis of Pure Na2CoPO4F as Cathode Material for Sodium Ion Batteries

Abstract: The expected theoretical energy density of Na 2 CoPO 4 F as a cathode material for sodium ion batteries surpasses 500 Wh kg −1 even if considering only one-electron utilized per formula unit. It is therefore one of the highest energy density cathode materials for sodium-ion batteries. In this work, pure phase Na 2 CoPO 4 F/C nanocomposite was successfully synthesized by a spray-drying and high temperature sintering method. The Na 2 CoPO 4 F/C nanocomposite, when tested vs. sodium metal, delivered a discharge c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…[ 142 ] Kawabe et al also revealed that carbon-coated Na 2 FePO 4 F/C could deliver approximately 110 mA h g −1 of reversible capacity, which corresponds to 90% of the theoretical capacity at a current rate of 6.2 mA g −1 , and 75% of the initial capacity was retained after 20 cycles, as shown in Figure 7 c. [ 144 ] Along with Na 2 FePO 4 F, orthorhombic Na 2 CoPO 4 F, which utilizes a redox couple of Co 2+ /Co 3+ , was reported as a highvoltage cathode for NIBs. [ 143,148,149 ] Although earlier works displayed poor electrochemical activity in Na-ion cells, [ 143 ] Zou et al recently demonstrated that Na 2 CoPO 4 F/C synthesized by the spray drying method can deliver a discharge capacity of 107 mA h g −1 with a voltage plateau at 4.3 V. [ 148 ] Monoclinic P2 1 /c Na 2 MnPO 4 F was also investigated as a cathode for NIBs. [ 142,146,147,153 ] The successful demonstration of the electrochemical activity of Na 2 MnPO 4 F electrode was fi rstly 3 .…”
Section: Fluorophosphatesmentioning
confidence: 99%
“…[ 142 ] Kawabe et al also revealed that carbon-coated Na 2 FePO 4 F/C could deliver approximately 110 mA h g −1 of reversible capacity, which corresponds to 90% of the theoretical capacity at a current rate of 6.2 mA g −1 , and 75% of the initial capacity was retained after 20 cycles, as shown in Figure 7 c. [ 144 ] Along with Na 2 FePO 4 F, orthorhombic Na 2 CoPO 4 F, which utilizes a redox couple of Co 2+ /Co 3+ , was reported as a highvoltage cathode for NIBs. [ 143,148,149 ] Although earlier works displayed poor electrochemical activity in Na-ion cells, [ 143 ] Zou et al recently demonstrated that Na 2 CoPO 4 F/C synthesized by the spray drying method can deliver a discharge capacity of 107 mA h g −1 with a voltage plateau at 4.3 V. [ 148 ] Monoclinic P2 1 /c Na 2 MnPO 4 F was also investigated as a cathode for NIBs. [ 142,146,147,153 ] The successful demonstration of the electrochemical activity of Na 2 MnPO 4 F electrode was fi rstly 3 .…”
Section: Fluorophosphatesmentioning
confidence: 99%
“…100 mA h g −1 and a potential plateau of 3.0 V . Carbon‐coated Na 2 CoPO 4 F shows a reversible capacity of 100 mA h g −1 with a potential plateau at 4.3 V (vs Na + /Na), achieving the highest specific energy (more than 400 mW h g −1 ) of the Na 2 MPO 4 F family . Na 2 MnPO 4 F displays a crystal structure differing from that of Na 2 MPO 4 F (M = Fe, Co), in which MnO 4 F 2 octahedra share common F vertices to form Mn 2 O 8 F 2 chains parallel to the b axis of the monoclinic unit cell, and these chains link the PO 4 tetrahedra in the a and c directions to form a 3D framework locating Na + ions in the channels .…”
Section: Polyanionic Compoundsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] Polyanionic cathode materials have a stable polyhedral framework, thus exhibiting excellent cycling performance and safety characteristics, which make them an attractive type of cathode materials for sodium ion batteries. 20,21 However, cathode materials with tetrahedral open framework structure have not been reported yet to date.…”
Section: Introductionmentioning
confidence: 99%